Transformation of Fiqh in the Forms of Pilgrimage and Zakat Legislation - Abdul Syatar; Arif Rahman (Mazahibuna: Jurnal Perbandingan Mazhab, 2019)
This article aims to provide an understanding of zakat and hajj legislation in Indonesia. The approach used is an analysis of the law itself. The Hajj and Zakat Law is a form of transformation of Islamic Jurisprudence in Indonesia. The latest hajj and zakat legislation are regulated in the Law of the Republic of Indonesia Number 8 of 2019 concerning the Organization of Hajj and Umrah and the Law of the Republic of Indonesia Number 23 of 2011 concerning Management of Zakat. It means that the government is responsible for the implementation of the pilgrimage for Muslims in Indonesia. These responsibilities include registration, determination of quotas, determination of deposits, guidance on hajj, etc. relating to the needs of pilgrims. The history of Islamic laws and regulations in Indonesia in the formation of zakat laws is a long and ironic journey. Zakat in fiqh is included not only as part of worship but also aspects of muamalah, especially the public aspect. Government policies in the field of worship provide the widest possible freedom.Keyword: Legislation; Zakat Act; Hajj Act; Zakat and Hajj.